Journey into darkness : follow the FBI's premier investigative profiler as he penetrates the minds and motives of the most terrifying serial killers /: follow the FBI's premier investigative profiler as he penetrates the minds and motives of the most terrifying serial killers. (2012) - Unknown
No abstract available